Conversations with Ken Kesey - Kesey, Ken (Book collections on Project MUSE., 2014)
Ken Kesey (1935-2001) is the author of several works of well-known fiction and other hard-to-classify material. His debut novel, One Flew Over the Cuckoo's Nest, was a critical and commercial sensation that was followed soon after by his most substantial and ambitious book, Sometimes a Great Notion . His other books, including Demon Box, Sailor Song, and two children's books, appeared amidst a life of astounding influence. He is maybe best known for his role as the charismatic and proto-hippie leader of the West Coast LSD movement that sparked ""The Sixties, "" as iconicall.